The impact of Role Conflict on the decrease in Perceived Productivity to the General Practitioner of Type A Hospital in Jakarta - Ludyani, Andi Tendry Dwi; Anindita, Rina; Mustikawati, Intan Silviana (Green Publisher Indonesia, 2023)
The purpose of this study is to explain the impact of transformational leadership and flexible work arrangements. The purpose of this study is to explain the effect of competence and role conflict on perceived productivity with work motivation as an intervening variable for general practitioners at Type A Hospital. Data collection was done using survey methods and online and offline questionnaires. The population in this study were general practitioners at the Type A Special Hospital in West Jakarta, who had been appointed as hospital employees. Instrument test for the validity of the questions and reliability using Product Moment Correlation Coefficient from Pearson and Alpha Cronbach. Data analysis technique is Path Analysis (path analysis). The results of the study show that there is an influence of competence and role conflict on work motivation and perceived productivity. Competence and role conflict through work motivation on perceived productivity. The suggestion from this study is that a leader must be able to inspire and motivate his employees towards the quality of work according to the vision and mission that the Hospital has made in achieving the Hospital's goals to improve the quality of service to patients.